Residence efficiency based on smart energy systems - Monteiro, André (2021)
The resources used to maintain all the activities in buildings are limited and, for this reason, it is critical the usage of energy efficiency measures. This paper is focused on a smart controller development able to automatically manage a building with the objective of improving its energy efficiency. The controller uses Artificial Neural Networks (ANN) as a forecast method and Fuzzy Logic Control (FLC) as a decision maker. The thermal house model is simulated using a MATLAB toolbox. One of the sub controllers is developed in this paper and is responsible for the HVAC control and optimization. The developed system uses renewable energy sources attached to an energy storage system to increase the overall energy efficiency. To demonstrate the effectiveness of the developed controller it is made an economic analysis of its influence in the build system.